RMPJ: An ImageJ plugin for morphological information processing in biomedical images - Kimori, Yoshitaka (PLoS computational biology, 2025)
RMPJ is an image-processing tool that facilitates the effective enhancement of low-contrast analysis objects and enables preprocessing to quantify the morphological features of the objects under analysis. This ImageJ plugin implements seven image-processing algorithms based on rotational morphological processing (RMP), a variation of traditional morphological operations. RMPJ enables the enhancement and extraction of intricate and nuanced features in biomedical images. Furthermore, it facilitates the separation and extraction of multiple aggregated structures. This software aims to expand the scope of research in life sciences by providing an image-processing method that quantitatively analyzes the morphological information of objects.